UPAYA HUMAS POLDA SUMBAR DALAM MEMULIHKAN REPUTASI KEPOLISIAN - henny suryani susanta; Sahman Sahman; Rahmat Fauzi (Jurnal Ranah Komunikasi, 2018)
Based on the results of the study, it can be concluded that the West Sumatra Regional Police Public Relations has sought to restore the reputation of the Police in the Post-Viral Case Two-Wheeled Motorists Allegedly Kicked by Members of the Traffic Police Brigadier Januar Rantos. The efforts made by the West Sumatra Regional Police Public Relations include thoroughly investigating the case, then the West Sumatra Regional Police Public Relations have the responsibility to choose the reputation of the West Sumatra Regional Police through media management, opinion contests (making news) and Cyber Patrols. As well as the efforts of the West Sumatra Regional Police to apologize and visit victims and provide assistance.